Organic Aggregation of Knowledge Object in Educational Systems - Gilbert Paquette; Ioan Rosca (The Canadian Network for Innovation in Education (CNIE), 2002)
We propose an organic approach to educational web-based systems where learning objects, operations on these objects, and actors that perform them are aggregated in meaningful ways. The users of a learning system must be able to observe it globally, at different levels and from diverse viewpoints. They must be able to propose adaptations and improvements constantly using means of observation integrated with the means of action. For this, we need to provide inspectable and executable models of the learning system, to be used as prisms for understanding and control of operations. We propose to reference these models with educational ontologies developed for instructional engineering. The implementation of some of these ideas in the Explor@-II system provides examples. Conversely, the next Explor@ implementation will benefit from the discussion presented here.